Modifikasi Arsitektur dalam Convolutional Neural Network untuk Klasifikasi Batik Lampung dan Batik Yogyakarta - Octavianus, Yonathan; Avianto, Donny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Batik is one of the unique forms of Indonesian culture. On October 2, 2009 UNESCO (United Nations Educational, Scientific, and Cultural Organization) designated batik as a Masterpiece of the Oral and Intangible Heritage of Humanity. One of the batik heritages of our ancestors is Lampung Batik and Yogyakarta Batik, where both batik have their own differences and uniqueness, so that we as Indonesian people must maintain and preserve the cultural heritage of our ancestors by creating a system that can determine both batik without using instinct or based on recommendations from others which can still cause errors. In previous studies, classification using Multikernel SVM managed to achieve an accuracy of 100%. There are also those who use CNN(Convolutional Neural Network)-Sobel with an accuracy of 91,2% in the training process and 91,8% in the validation process. The problems experienced in previous studies were the limitations of the dataset and the model testing process which was still not optimal so that it did not get satisfactory results so that in this study the Convolutional Neural Network method will be used with 6 architectures, 3 of which are unModified architectures, namely MobileNetV2, DenseNet121, and Xception. And 3 Modified architectures, namely MobileNetV2 (Modified), DenseNet121 (Modified), and Xceptipn (Modified). The selection of the three architectures is because it has a very large number of layers so that it can calculate a very large amount of data and produce the appropriate output. The best results obtained in this study were the Modified architecture, namely Xception (Modified) with an accuracy of 100%, Precision 97%, Recall 94%. F1 Score 92%, and Loss 0,0066 in the 30th epoch experiment and learning rate 0,0001 so that Xception became the best model in the Modified architecture (Modified). This research is expected to be able to provide a renewable technology system to ordinary people who do not know Lampung Batik and Yogyakarta Batik to be able to distinguish between the two specifically so as to minimize errors in analyzing or when buying the desired Batik